Anti-PD-L1/PD-L2 therapeutic vaccination in untreated chronic lymphocytic leukemia patients with unmutated IgHV - Klausen, Uffe; Grauslund, Jacob Handlos; Jørgensen, Nicolai Grønne Dahlager; Ahmad, Shamaila Munir; Jonassen, Merete; Weis-Banke, Stine Emilie; Martinenaite, Evelina; Pedersen, Lone Bredo; Lisle, Thomas Landkildehus; Gang, Anne Ortved; Enggaard, Lisbeth; Hansen, Morten; et al. (Frontiers in Oncology, 2022)
Chronic lymphocytic leukemia (CLL) patients with unmutated immunoglobulin heavy chain (IgHV) are at risk of early disease progression compared to patients with mutated IgHV. As a preventive strategy, we treated 19 previously untreated CLL patients with unmutated IgHV in a phase 1/2 trial (clinicaltrials.gov, NCT03939234) exploring the efficacy and toxicity of a therapeutic cancer vaccine containing peptides derived from programmed death ligand 1 (PD-L1) and ligand 2 (PD-L2), hoping to restore immunological control of the disease. According to the International Workshop on Chronic lymphocytic Leukemia (iwCLL) response criteria, no patients obtained a response; however, during follow-up, one patient had complete normalization of the peripheral lymphocyte count and remained in biochemical remission after a follow-up time of 15 months. At the end of treatment, one patient had progressed, and 17 patients had stable disease. During follow-up with a median time of 23.5 months since inclusion, seven patients had progressed, and eight patients had stable disease. The median time to first treatment (TTFT) from diagnosis was 90.3 months with a median follow-up time of 50.1 months. This apparent favorable outcome in TTFT needs to be investigated in a randomized setting, as our population may have been biased. More than 80% of patients obtained vaccine-specific immune responses, confirming the immunogenicity of the vaccine. The vaccine was generally well tolerated with only grade I–II adverse events. Although there were some signs of clinical effects, the vaccine seems to be insufficient as monotherapy in CLL, possibly due to a high tumor burden. The efficacy of the vaccine should preferably be tested in combination with novel targeted therapies or as a consolidating treatment.